2020
DOI: 10.1136/bmjspcare-2019-002108
|View full text |Cite
|
Sign up to set email alerts
|

Quality of cancer end-of-life care: discordance between bereaved relatives and professional proxies

Abstract: BackgroundQuality of care for patients dying in hospital remains suboptimal. A major problem is the identification of valid sources of information about the views and experiences of dying patients and their relatives.AimThis study aimed to estimate the agreement on quality of end-of-life care from the perspectives of bereaved relatives, physicians and nurses interviewed after the patients’ death.DesignIn this prospective study, we interviewed, after the patient death, the bereaved relatives, the attending phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…However, the agreement between the FMs and HCPs was poorest for symptoms such as pain and anxiety, 7 which is congruent with our findings. Bertocci et al, 3 showed that there was poor agreement between FMs, nurses and physicians in home care, other wards and other hospitals. This result was also shown in a study in two medical ICUs at academic tertiary care medical centres, where the authors compared proxy data collection between quality of dying from family caregivers compared with caregiving physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the agreement between the FMs and HCPs was poorest for symptoms such as pain and anxiety, 7 which is congruent with our findings. Bertocci et al, 3 showed that there was poor agreement between FMs, nurses and physicians in home care, other wards and other hospitals. This result was also shown in a study in two medical ICUs at academic tertiary care medical centres, where the authors compared proxy data collection between quality of dying from family caregivers compared with caregiving physicians.…”
Section: Discussionmentioning
confidence: 99%
“…ward setting, Bertocci et al, 3 showed that FMs and HCPs have low congruity when assessing the patient's end-of-life care. They however also showed that HCPs play an important role in complementing data when FMs did not provide the information.…”
Section: Original Researchmentioning
confidence: 99%